The Effect of Soybean Price Stability on Tofu Sales Productivity with Industrial Development Patterns as a Mediating Variable in Tofu Businesses in the Tulungagung Region - Rochman, Abdul (Yayasan Azka Hafidz Maulana, 2024)
The objective of this study is to analyse the impact of stable soybean prices on the productivity of tofu sales, taking into account the mediating variable of industrial growth patterns in tofu firms located in the Tulungagung region. This study employs a quantitative technique as its research method. The data processing in this study uses the smartPLS SEM (Partial Least Squares - Structural Equation Modelling) programme. PLS has the capacity to elucidate the correlation between variables and conduct comprehensive analyses within a single test. In order to test the hypothesis, specifically utilising statistical values, the t-statistic value utilised with an alpha level of 5% is 1.96. Findings of the research: The first hypothesis testing confirmed that the Industrial Development Pattern (Z) really influenced Sales Productivity (Y). The findings of testing the second hypothesis confirm that there is a significant effect of Price Stability (X) on Sales Productivity (Y). The findings of testing the third hypothesis confirm that Price Stability (X) has a significant impact on Sales Productivity (Y). The findings of testing the fourth hypothesis have been validated. The variable X, which represents price stability, has a significant influence on the variable Y, which represents sales productivity, via means of the variable Z, which represents industrial development patterns.